2007
DOI: 10.1152/physiol.00008.2007
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an “Ear” to the Ground: Seismic Communication in Elephants

Abstract: This review explores the mechanisms that elephants may use to send and receive seismic signals from a physical, anatomical, behavioral, and physiological perspective. The implications of the use of the vibration sense as a multimodal signal will be discussed in light of the elephant's overall fitness and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 51 publications
1
82
0
Order By: Relevance
“…Moreover, it has been demonstrated that macroscelids (at least, some species of Elephantulus) use foot-drumming for communication and defence (Faurie et al 1996). Foot-drumming is a common practice among mammals displaying low frequency hearing capacities, such as proboscideans (O'Connell-Rodwell 2007), lagomorphs, kangaroo-rats and gerbils (Randall 2001), because it produces low frequency seismic sound waves that cannot be heard by other mammals (Randall 2001). Finally, in modern macroscelids, the stapedial artery is partly or fully enclosed in a bony tube and in some genera, such as Rhynchocyon and Macroscelides, the carotid artery is enclosed in a bony tube, too.…”
Section: Implications On the Evolution Of The Ear And Hearing In Macrmentioning
confidence: 99%
“…Moreover, it has been demonstrated that macroscelids (at least, some species of Elephantulus) use foot-drumming for communication and defence (Faurie et al 1996). Foot-drumming is a common practice among mammals displaying low frequency hearing capacities, such as proboscideans (O'Connell-Rodwell 2007), lagomorphs, kangaroo-rats and gerbils (Randall 2001), because it produces low frequency seismic sound waves that cannot be heard by other mammals (Randall 2001). Finally, in modern macroscelids, the stapedial artery is partly or fully enclosed in a bony tube and in some genera, such as Rhynchocyon and Macroscelides, the carotid artery is enclosed in a bony tube, too.…”
Section: Implications On the Evolution Of The Ear And Hearing In Macrmentioning
confidence: 99%
“…Békésy described a second method used by roosters, and more recently shown to be used by elephants (O'Connell-Rodwell, 2007), to reduce inner ear input during calling. This involves closing off the external auditory meatus just prior to vocalizations.…”
Section: Amphibiansmentioning
confidence: 99%
“…For a review about the communication tools adopted by elephants, see O'Connell-Rodwell et al (2000) and O'Connell-Rodwell (2007).…”
Section: Seismic Signals From Mammalsmentioning
confidence: 99%